The State as Innovator - Pohulak-Żołędowska, Elżbieta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article shows that breakthrough innovation is improved when the State actively finances R&D. The State must financially support the innovation process when the markets are incomplete or when high-risk capital does not come through. The State’s innovation policy should serve to realise the concept of sustainable development and foster cooperation between participants in the innovation process.